Factors Influencing Electronic Tax Compliance Of Small and Medium-Sized Enterprises in Northern of Vietnam - Hung, Dinh The; Ha, Le Thi Thanh; Giang, Nguyen Thi Huong; Yen, Nguyen Kim; Linh, Nguyen Khanh; Le, Han Ngoc Le (Journal of Ecohumanism, 2024)
The electronic tax service system - eTax in Vietnam is implemented as an administrative reform initiative of the tax industry to improve efficiency of the tax authorities. This research therefore sets out to examine the variables that impact firms’ compliance levels in the context of adopting electronic tax with a model that tests linear relationship between identified factors and tax compliance. Research data serving the study were collected from July to October 2023 from respondents working for small and medium-sized enterprises (SMEs) in Northern Vietnam with 200 valid questionnaires. Research findings reveal a positive relationship between The level of electronic tax application (AE), Tax policy - tax inspection & examination (TPTI) and The level of tax compliance (TC). Moreover, the level of adoption of electronic tax is positively influenced by Perceived ease of use (PEOU), Perceived usefulness (PU) and Information techonology skills (IT). Based on the research results, the study proposes appropriate recommendations to enhance the management mechanism and improve the tax compliance level of the SMEs in Northern Vietnam.